Gastronomic Potential in the Development of Tourism in Gorontalo - Yesi Pandu Pratama Wibowo DC; Jati Paras Ayu; Ayu Rakhmi Tiara Hamdani; Dewi Rachmawati; Siti Adelita Raif Khadijah (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2026)
This study examines the potential of gastronomic tourism in Gorontalo City, highlighting opportunities for its development as a key attraction. Employing a qualitative approach, data are presented in descriptive narratives and analyses. The study site, Gorontalo City, was selected due to its rich culinary and gastronomic heritage, which offers unique opportunities to attract visitors. Primary data were obtained through field observations, in-depth interviews with culinary and gastronomy experts, and focus group discussions (FGDs) to validate findings. Secondary data were derived from online documents, literature, and scientific journals. A purposive sampling method was applied to select culinary items based on historical and cultural significance, accessibility to food preparation processes, and popularity among local and visiting tourists. The collected data were analyzed through stages of data reduction, presentation, and conclusion drawing, supported by relevant theories and concepts. A SWOT analysis was conducted to identify strengths, weaknesses, opportunities, and threats related to gastronomic tourism in Gorontalo and a TOWS Matrix to generate strategies based on the findings from a SWOT analysis. Findings reveal that while Gorontalo offers strong symbolic culinary traditions and community-based tourism models, several barriers persist, including weak documentation, underdeveloped beverage traditions, limited digital promotion, and fragile MSME ecosystems, particularly for women-led enterprises. Nonetheless, emerging initiatives, such as food festivals, immersive homestays, and government-supported culinary hubs, indicate growing interest in gastronomic tourism. This paper recommends a multi-sectoral strategy that includes the development of a culinary heritage certification, innovation in traditional beverages, digital storytelling campaigns, and capacity-building for MSMEs. The integration of sustainability principles, through eco-friendly practices and community participation, is emphasized as a foundation for long-term success. Gorontalo’s culinary identity, if strategically developed and promoted, holds significant potential to become a catalyst for cultural preservation, inclusive economic growth, and regional tourism competitiveness.